Assessing agricultural land suitability in the Fakkeh region, Iran. (March 2017) - Albaji, Mohammad; Alboshokeh, Abrahim
Land suitability assessments can provide useful information to help optimize agricultural land use. Due to the current lack of appropriate land management practices in the Fakkeh region, southwest Iran, a land suitability evaluation study for key agricultural crops, including wheat, alfalfa, maize and barley, covering 43, 700 ha was undertaken. Qualitative evaluation was carried out using two methods, the simple limitation and parametric methods (Storie and square root method), to compare land and climate characteristics with crop needs. The most important limiting factors in wheat, alfalfa and barley production included the physical properties of the soil, especially light soil texture. The major limiting factors in maize production were low relative humidity and high n / N ratio during the plant growth period, light soil texture, soil salinity and alkalinity.